Is unpaid work conducive of well-being? The case of within-household unpaid work in the Modena District. (2015) - Addabbo, Tindara; Bilancini, Ennio
In this paper, we document the pattern of unpaid domestic and care work, disaggregated on the basis of the type of work and the care recipient, and its partial correlation with subjective well-being as measured by reported life satisfaction. We explore gender-specific effects since domestic and unpaid work has an intrinsic relational dimension that, at least in the current Italian society, has an important gender-specific component. The data used come from the 2012 Survey on the Economic and Social Conditions in the Modena District (ICESmo3) which is a unique dataset that contains disaggregated data on unpaid work. In particular, this dataset allows us to look at the correlations between the different types of unpaid work and reported life satisfaction. The overall picture that emerges from the data is one where unpaid work within the household is more likely to be conducive of well-being if it is more likely to be genuinely voluntary and intrinsically motivated. Although we must admit that this conclusion is highly speculative, we think it is a good starting point for further analyses in this regard.